2018
DOI: 10.33225/jbse/18.17.551
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Visualization Type and Student Spatial Abilities on Learning Achievement

Abstract: Students’ spatial ability plays an important role in instruction with dynamic and static visualizations. This research was aimed at describing 1) the difference in learning achievement between the students who learned from dynamic visualization and static visualization, 2) the difference in learning achievement among students who have high spatial ability and those who have low spatial ability, and 3) the interaction between type of visualization and spatial ability on learning achievement. This research used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
(97 reference statements)
0
6
0
3
Order By: Relevance
“…While there has been much mention of both personality and cognitive factors relating to learning with external representations (see ChanLin 2001;Klein 2003), no research has been found to assess or control for these factors in student-generated SMA. For example, many researchers argued that spatial ability is crucial for any modeling activity, especially when students are engaged with dynamic and static visualization (Höffler 2010;Sudatha et al 2018). Spatial ability is defined as the ability of "thinking about the shapes and arrangements of objects in space and about spatial processes, such as the deformation of objects, and the movement of objects and other entities through space" (Marunic and Glazar 2014).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…While there has been much mention of both personality and cognitive factors relating to learning with external representations (see ChanLin 2001;Klein 2003), no research has been found to assess or control for these factors in student-generated SMA. For example, many researchers argued that spatial ability is crucial for any modeling activity, especially when students are engaged with dynamic and static visualization (Höffler 2010;Sudatha et al 2018). Spatial ability is defined as the ability of "thinking about the shapes and arrangements of objects in space and about spatial processes, such as the deformation of objects, and the movement of objects and other entities through space" (Marunic and Glazar 2014).…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…This research shows that the use of dynamic visualization can improve the students' understanding about transportations system and excretion in organism. Some studies got similar results (Lin & Dwyer, 2010;Sudatha, Degeng, & Kamdi, 2018;Wu, Lin, & Hsu, 2013). According to (Ali & Ambusaidi, 2017), dynamic visualization helps the students in conceptualizing abstract concepts that might be difficult to be understood by the students.…”
Section: Discussionmentioning
confidence: 82%
“…Particularly in Science Education, DLOs have been acknowledged as invaluable tools to support the achievement of high-level learning outcomes. Simulations, dynamic visual representations and visualizations of natural phenomena and quantities, among other types of DLOs, play in important role in learning processes and learning achievements [9][10][11][12][13][14][15].…”
Section: Digital Learning Objects In Science Educationmentioning
confidence: 99%
“…Over the last years, several efforts have been made to develop methods, frameworks and tools for assessing DLOs. After a thorough review of the relevant literature searching for scientifically substantiated and comprehensive models for evaluating DLOs, SREB-SCORE (Southern Regional Education Board) [19], LORI (Learning Object Review Instrument) [20], LOEM (Learning Object Evaluation Metric) [15], LOES-T (Learning Object Scale for Teachers) [21], LOES-S (Learning Object Scale for Students) [22], and MERLOT (Multimedia Educational Resource for Learning and Online Teaching) [23], are among the well documented and most widely used tools for the evaluation of educational resources and especially Learning Objects.…”
Section: Digital Learning Objects In Science Educationmentioning
confidence: 99%